Habitat des personnes âgées, l’intergénérationnalité au pouvoir ? - Maël Gauneau; Manon Labarchède; Guy Tapie (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Many people recognise the strong sense of identity that housing has for people and their families, particularly in the context of ageing. The concept of intergenerational living is opposed to the principles of many housing structures that favour the interdependence of the individual. It sets a new horizon, that of an understanding between the generations who, by living alongside each other, exchange and provide mutual services. It would also be a bulwark against the sudden exclusion of the elderly. This article analyses the production channels of intergenerational housing based on two types: intergenerational residences, which focus on senior-family relationships, and cohabitation, which focuses on senior-student or young working-class relationships. Based on a socio-spatial analysis of operations and situations related to intergenerational housing, combining semi-directive interviews (30) and in situ observations, our work highlights a complex implementation of intergenerational living, which cannot be considered as a “turnkey” formula, based solely on the fact that several generations live side by side. The sharing and appropriation of common spaces, favouring encounters and exchanges, is one of the main axes of the development of this type of housing, but does not necessarily ensure its success. In order to be effective, intergenerational living requires that each person offers a minimum of availability to the other, in order to live together and build a common project.